Neonatal septicemia: isolates and their sensitivity pattern with emergence of Citrobacter septicemia - Sharma, Ram Sunder; Tiwari, Manali; Bansal, Ram Pratap (International Journal of Research in Medical Sciences, 2016)
Background: Septicemia in neonates refers to bacterial infection documented by positive blood culture in the first 28 days of life and is one of the leading causes of neonatal mortality and morbidity in India. The aim of the study was to identify clinical neonatal sepsis cases and isolate responsible microorganism by blood culture and determine sensitivity pattern of isolates in a tertiary care hospital. Methods: It is a hospital based retrospective study involving neonates admitted in department of paediatrics at a medical college hospital. Two hundred twenty five blood samples were collected for blood culture from neonates with clinical sepsis with standard protocol. Isolation of microorganism and antibiotic sensitivity testing was done with disc diffusion method. Results: Blood culture reports were positive in 43.55% cases of clinical sepsis. Among positive blood culture reports gram negative isolates were more frequent (75.51%). Most commonly isolated was Klebsiella species (34.70%), most common gram positive isolate was Streptococcus (10.20%). Prevalence of Citrobacter species isolation was 16.12%. Among gram negative isolates best overall sensitivity was towards levofloxacin (97.3%) followed by amikacin (60.8%). Sensitivity to piperacillin+tazobactam (20.3%) and cefoperazone+sulbactam (23%) were very low. Gram positive isolates had best sensitivity to vancomycin and linezolid. Conclusions: Gram negative organisms (Klebsiella species, Citrobacter species), Streptococcus, Staphylococcus are leading cause of neonatal sepsis. There are high levels of resistance to routinely used antibiotics among them. Therefore results of this study suggest that we should revise our antibiotic treatment policy and emphasize on rationale antibiotic use.